International Organizations and Research Methods An Introduction - Badache, Fanny; Kimber, Leah R.; Maertens, Lucile (University of Michigan Press, 2023)
Scholars have studied international organizations (IOs) in many disciplines, thus generating important theoretical developments. Yet a proper assessment and a broad discussion of the methods used to research these organizations are lacking. Which methods are being used to study IOs and in what ways? Do we need a specific methodology applied to the case of IOs? What are the concrete methodological challenges when doing research on IOs? International Organizations and Research Methods: An Introduction compiles an inventory of the methods developed in the study of IOs under the five headings of Observing, Interviewing, Documenting, Measuring, and Combining. It does not reconcile diverging views on the purpose and meaning of IO scholarship, but creates a space for scholars and students embedded in different academic traditions to reflect on methodological choices and the way they impact knowledge production on IOs.